Alice May : Gilbert and Sullivan's first prima donna - Simpson, Adrienne (Forgotten stars of the musical theatre., 2003)
This biography tells the story of Alice May, a touring prima donna in the nineteenth century who took part in pioneering performances of the popular light operas of the day, including the first production of Gilbert and Sullivan's The Sorcerer.